2021
DOI: 10.1111/1365-2664.14090
|View full text |Cite
|
Sign up to set email alerts
|

Using habitat suitability and landscape connectivity in the spatial prioritization of public outreach and management during carnivore recolonization

Abstract: Despite continued global declines in large carnivore abundance and distribution, some species are recovering. In North America, these recoveries can occur in large areas of suitable habitat in or near areas of human development, increasing the likelihood of human–carnivore conflicts. Understanding the intersection among habitat suitability, connectivity and human–carnivore conflicts can aid in conflict prevention and mitigation. We used GPS collar data from 97 bears and conflict reports collected from 1991 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Aside from the composition of landscape, the configuration, i.e., the spatial organization of the landscape elements, can also determine the bears' behavior, and hence HBC (Linke et al, 2005;Boudreau et al, 2022). We found that HBC are more likely to occur in fragmented forests, as found elsewhere (Bombieri et al, 2018;Khosravi et al, 2022).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Aside from the composition of landscape, the configuration, i.e., the spatial organization of the landscape elements, can also determine the bears' behavior, and hence HBC (Linke et al, 2005;Boudreau et al, 2022). We found that HBC are more likely to occur in fragmented forests, as found elsewhere (Bombieri et al, 2018;Khosravi et al, 2022).…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, landscape composition and configuration can determine the availability and access to resources, affecting bears' behaviors and humanbear interactions (Tee et al, 2021;Khosravi et al, 2022). As found previously, HBC is more likely to occur in landscapes characterized by a complex mosaic of forest habitat patches (Boudreau et al, 2022;Khosravi et al, 2022). Therefore, conflict mitigation efforts should consider the effects of these factors on HBC.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Our findings demonstrate that variations in environmental factors including drought, and conflicts within parks early in the year could be a warning of increased frequency of high or moderate severity conflicts later in the year. As unsecured human foods and edible garbage are primary causes of human-black bear conflicts [28][29][30][31]66], it is important to secure attractants (i.e., removing food sources or establishing physical barriers [62,65,67]) to facilitate coexistence of humans and black bears, which can mitigate the frequency and severity of conflicts.…”
Section: Plos Onementioning
confidence: 99%
“…Proximity of wildlands and residential food sources for bears present a risk of conflict with people [25][26][27]. Consequently, human food conditioning by black bears, and unsecured foods and edible garbage are root causes of human-bear conflicts, and are also the primary factors that can be managed to facilitate coexistence [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%